Restoring the smile: Inexpensive biologic restorations - Neeti P Mittal (Wolters Kluwer Medknow Publications, 2014)
Extensive breakdown of primary teeth to the cervical level and their loss in very young children is not uncommon. Owing to increasing concerns over self-appearance, due considerations to esthetic aspects in addition to restoring function are necessary aspects of rehabilitation of mutilated teeth to help children grow into a psychologically balanced personality. The present article describes rehabilitation of grossly decayed teeth with biologic restorations such as dentine posts, dentine post and core and biologic shell crown. This treatment modality provided a cost-effective esthetic solution.